Environmental Responsibility as a Core Dimension of Corporate Social Responsibility: A Conceptual Framework - Jaiswal, Sejal; Kharwar, Sheetal Singh (Journal of Economics and Management, 2026)
Global business organizations face increasing pressures to address sustainability challenges related to climate change, environmental degradation, and depletion of resources. Corporate Social Responsibility (CSR) has evolved from a voluntary/philanthropic practice to a governance-based practice that is integral to business decisions and financial reporting. During this journey, environmental responsibility has become an integral and financially material aspect of corporate social responsibility. This paper proposes a conceptual framework on how environmental responsibility becomes an integral part of corporate social responsibility and is related to ESG reporting, sustainable finance, and global financial governance. Using stakeholder theory, legitimacy theory, institutional theory, and sustainable finance theories, this paper proposes a conceptual framework on how environmental responsibility is not only an ethical requirement but also a risk management tool for business organizations and a determinant of corporate legitimacy. ESG reporting is conceptualized as a corporate governance tool for implementing environmental responsibility, while sustainable finance instruments such as green bonds and ESG-based lending rates become financial rewards for business organizations practicing environmental responsibility. Situating environmental responsibility in global financial governance is also an important aspect of this study, which seeks to highlight the normative and strategic role of environmental responsibility in sustainable business practices. This paper contributes to the literature on corporate social responsibility and sustainability by developing an integrated theoretical framework on how environmental responsibility is related to corporate financial and ethical responsibilities and how it becomes an integral part of corporate governance and global financial governance.